Feeding sunflower meal with pullets and laying hens even at a 30% inclusion rate does not impair the ileal digestibility of most amino acids - Such, Nikoletta; Mezőlaki, Ákos; Tewelde, Kesete Goitom; Pál, László; Horváth, Boglárka; Poór, Judit; Dublecz, Károly (Frontiers in Veterinary Science, 2024)
Utilization of locally available protein sources in poultry nutrition is challenging for theUsing more locally available protein sources in poultry nutrition means an actual challenge for the feed manufacture and companies and farmers. Sunflower meal (SFM) is available in high quantities in several European countries and could be used probably as a poultry feedstuff at higher inclusion rates. However, its maximum inclusion rate in the diets of different poultry species and age categories is not known. Pullets and laying hens can probably tolerate higher amounts of SFM, but only limited information are available on these poultry groups. So, a digestibility trial was carried out with 8-week-old layer type pullets and 50-week-old laying hens and beside a basal diet, SFM was fed at 10, 20 and 30%. Feeding SFM significantly improved the digestibility, among essential amino acids (AA) of threonine, valine, lysine, tyrosine, glycine, aspartic acid and arginine in the pullet diets. No such improvement was found with laying hens. Only the absorption of the two branch chained AAs, leucin (pullets) and isoleucine (hens) declined due to SFM. The AA digestibility of the SFM itself was also calculated by linear regression. The coefficients were in all cases higher in hens that in pullets. Comparing the measured digestibility coefficients of SFM with table values, it can be concluded, that high variance exists because of the differences in the methodology and the test animal in the digestibility trials. From the present trial it can be concluded, that SFM can entirely replace extracted soybean meal in pullet and layer diets, without negative effect on the protein digestion of birds.